Effects of bipyramidal gold nanoparticles and gold nanorods on the detection of immunoglobulins. Issue 21 (19th August 2016) - Zhang, Hua; She, Zhe; Su, Han; Kerman, Kagan; Kraatz, Heinz-Bernhard
Abstract : The influence of different shapes of gold nanoparticles and techniques (SPR and SWV) on the sensitivity of biosensors was investigated, using IgG detection as a model system. Abstract : Two types of gold nanoparticles are compared for their use in a sensor for immunoglobulin detection – bipyramidal gold nanoparticles (GBPs) and gold nanorods (GNRs). Using surface plasmon resonance spectroscopy and square wave voltammetry allowed us to evaluate the utilities of these two types of gold nanoparticles in a label-free detection of the analyte IgG. However both systems showed a significant enhancement in sensitivity over a nanoparticle free system, showing a 64-fold enhancement for the GBP-containing sensor and a 16-fold enhancement for the GNR-containing sensor systems.